2003
DOI: 10.1103/physrevb.68.235317
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Bragg’s rule for heavy-ion stopping in silicon carbide

Abstract: The stopping powers for O, Al, Cr, Mn, Co, and Cu in a self-supporting SiC film have been measured in transmission geometry over a continuous range of energies using a time-of-flight elastic recoil detection analysis system. These stopping data, along with the stopping data in Si and C obtained using the same ions and measurement technique, are used to assess the validity of the Bragg additivity rule for stopping powers in SiC over a range of ions and energies. Within experimental uncertainties ͑Ϯ4%͒, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…An early comprehensive review of stopping in inorganic materials showed no deviations from Bragg's rule within a few percent precision [20]. More recent research on these cases either confirm Bragg's rule within ±4% [23,24] or show deviations of up to 7% [24].…”
Section: Derivation Of the Yield Formulamentioning
confidence: 96%
“…An early comprehensive review of stopping in inorganic materials showed no deviations from Bragg's rule within a few percent precision [20]. More recent research on these cases either confirm Bragg's rule within ±4% [23,24] or show deviations of up to 7% [24].…”
Section: Derivation Of the Yield Formulamentioning
confidence: 96%
“…These include: measuring the energy loss of alpha particles from alpha emitters (i.e. 241 Am and 212 Bi) and converting to thickness from tabulated energy loss values [12], measuring the energy loss of an alpha beam [10,11,36,37,40,[64][65][66][67], measuring the energy loss of a Li beam [26] and determining the thickness using tabulated stopping power values [68], direct measurement of the film thickness from cross sectional micrographs using TEM with surface roughness evaluated by Scanning Electron Microscopy (SEM) [11,[69][70][71], weight and area measurements [26,30,56,72], by Rutherford Backscattering Spectrometry (RBS) on films grown on bulk substrates [62,65,70,73], and by NIR spectrometry by comparing simulated and measured reflection spectra [18]. AFM [6,67,73], and profilometry [62], have been used to determine the surface roughness and its contribution to the uncertainty.…”
Section: Thickness Determinationmentioning
confidence: 99%
“…The measurement of the energy loss of ions in materials is of crucial importance in a number of academic and industrial fields [1][2][3][4][5]. For example, an accurate knowledge of the stopping power is essential for compositional and structural analysis of thin films and surfaces utilizing Ion Beam Analysis (IBA) techniques, [6][7][8][9] in computational and experimental studies of radiation effects and radiation damage in materials and electronics under extreme conditions, [10] in electronic device fabrication, [11] nuclear physics, [12] astrophysics, [13] and medical physics, [14]. Despite the fundamental importance of measured stopping power data to these fields, there are still numerical disagreements between energy loss models and measured values for various combinations of ion and target [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation effects in silicon carbide (SiC) have been studied for both scientific and practical reasons [26][27][28][29][30]. Due to their high strength, excellent high-temperature properties, good corrosion resistance and low neutron absorption cross-section, silicon carbide fiber/silicon carbide matrix composites are considered as perspective materials for the advanced nuclear applications, e.g., structural materials and fuel coatings in fission reactors, structural components in fusion reactor [31].…”
Section: Introductionmentioning
confidence: 99%